The Development of Syllable Flashcard Media to Improve Early Reading and Writing Skills in Grade I Students at MI Assegaf Palembang - Putri, Shabira Panca; Tutut Handayani; Muhamad Afandi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study discusses the challenges of low early literacy skills in first-grade students at MI Assegaf Palembang, exacerbated by monotonous teaching methods and minimal use of engaging media. The aim of the research is to develop and evaluate picture and color-coded syllable flashcard media to improve students' reading and writing abilities. The study uses a Research and Development (R&D) approach with the ADDIE model, involving all first-grade students as a saturated sample. Data were collected through expert validation questionnaires, student response surveys, pretest-posttest instruments, and documentation. Quantitative and qualitative analyses were conducted to assess the validity, practicality, and effectiveness of the media. The results show that the flashcard media is highly valid (average expert score of 98.1%), highly practical (student response of 96.8%), and significantly improves students' reading and writing abilities, as evidenced by posttest scores exceeding the minimum completeness criteria. In conclusion, the developed flashcard media is effective and recommended for early literacy learning.